Dynamic Alignment of the Forward-Proton Detectors at the LHC. (9th August 2012) - Staszewski, R.; Trzebiński, M.; Chwastowski, J.
Abstract : The dynamic alignment method of the forward proton detectors proposed by the CDF collaboration is reviewed. The applicability of the method at the LHC is discussed.